Identification of "sarsasapogenin-aglyconed" timosaponins as novel Aβ-lowering modulators of amyloid precursor protein processing. Issue 5 (10th February 2016) - Sy, Lai-King; Lok, Chun-Nam; Wang, Juan-Yu; Liu, Yungen; Cheng, Lu; Wan, Pui-Ki; Leung, Chi-Ting; Cao, Bei; Kwong, Wai-Lun; Chang, Raymond Chuen-Chung; Che, Chi-Ming
Abstract : The "sarsasapogenin-aglyconed" timosaponins are Aβ lowering agents that may be useful for the development of Alzheimer's disease therapeutics. Abstract : The inhibition of amyloid β (Aβ) peptide production is a key approach in the development of therapeutics for the treatment of Alzheimer's disease (AD). We have identified that timosaponins consisting of sarsasapogenin (SSG) as the aglycone can effectively lower the production of Aβ peptides and stimulate neurite outgrowth in neuronal cell cultures. Structure–activity relationship studies revealed that the cis -fused AB ring, 3β-configuration, spiroketal F-ring and 25 S -configuration of SSG are the essential structural features responsible for the Aβ-lowering effects and neurite-stimulatory activity. New synthetic derivatives that retain the SSG scaffold also exhibited an Aβ lowering effect. Treatment of cells with timosaponins led to modulation of amyloid precursor protein (APP) processing through the suppression of β-cleavage and preferential lowering of the production of the 42-amino acid Aβ species (Aβ42 ) without affecting another γ-secretase substrate. The SSG and "SSG-aglyconed" timosaponins also penetrated brain tissue and lowered brain Aβ42 levels in mice. Our studies demonstrate that timosaponins represent a unique class of steroidal saponins that may be useful for the development of AD therapeutics.